Investigation of Magnetoelectric Sensor Requirements for Deep Brain Stimulation Electrode Localization and Rotational Orientation Detection - Mevlüt Yalaz; Günther Deuschl; Markus Butz; Alfons Schnitzler; Ann-Kristin Helmers; Michael Höft (Sensors, 2021)
Correct position and orientation of a directional deep brain stimulation (DBS) electrode in the patient’s brain must be known to fully exploit its benefit in guiding stimulation programming. Magnetoelectric (ME) sensors can play a critical role here. The aim of this study was to determine the minimum required limit of detection (LOD) of a ME sensor that can be used for this application by measuring the magnetic field induced by DBS. For this experiment, a commercial DBS system was integrated into a head phantom and placed inside of a state-of-the-art Superconducting Quantum Interference Device (SQUID)-based magnetoencephalography system. Measurements were performed and analyzed with digital signal processing. Investigations have shown that the minimum required detection limit depends on various factors such as: measurement distance to electrode, bandwidth of magnetic sensor, stimulation amplitude, stimulation pulse width, and measurement duration. For a sensor that detects only a single DBS frequency (stimulation frequency or its harmonics), a LOD of at least 0.04 pT/Hz<semantics>0.5</semantics> is required for 3 mA stimulation amplitude and 60 μ<semantics>μ</semantics>s pulse width. This LOD value increases by an order of magnitude to 0.4 pT/Hz<semantics>0.5</semantics> for a 1 kHz, and by approximately two orders to 3 pT/Hz<semantics>0.5</semantics> for a 10 kHz sensor bandwidth. By averaging, the LOD can be reduced by at least another 2 orders of magnitude with a measurement duration of a few minutes.